Using an interactive DVD about type 2 diabetes and insulin therapy in a UK South Asian community and in patient education and healthcare provider training. Issue 9 (September 2015) - Patel, Naina; Stone, Margaret A.; Hadjiconstantinou, Michelle; Hiles, Steve; Troughton, Jacqui; Martin-Stacey, Lorraine; Daly, Heather; Carey, Marian; Khulpateea, Anita; Davies, Melanie J.; Khunti, Kamlesh
Highlights A multilevel approach to dispel myths about insulin therapy in type 2 diabetes. Integral to this was the use of an interactive educational DVD. Statistically significant changes in attitudes among community participants. Can help patients accept and consolidate decision to commence this treatment. The training and resources are an effective way to support healthcare professionals.